2017
DOI: 10.3390/ijms18050924
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Fluorescence Imaging in Nano-Therapeutics and Photo-Thermal Evaluation

Abstract: The unresolved and paramount challenge in bio-imaging and targeted therapy is to clearly define and demarcate the physical margins of tumor tissue. The ability to outline the healthy vital tissues to be carefully navigated with transection while an intraoperative surgery procedure is performed sets up a necessary and under-researched goal. To achieve the aforementioned objectives, there is a need to optimize design considerations in order to not only obtain an effective imaging agent but to also achieve attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 86 publications
(102 reference statements)
0
19
1
Order By: Relevance
“…We utilized healthy swine that did not have any bladder pathology, given that no porcine bladder cancer model exists presently. Healthy urothelial mucosa has been shown to be less permeable than tumor tissue, hence we believe that intravesical chemotherapy with HT may actually result in an even greater increase of MMC absorption in patients with bladder cancer than demonstrated in our study [17]. Our findings deferred from van Valenberg et al, where they found that MMC concentration did not differ between the cold MMC group and radiofrequency induced MMC group in normal urothelial tissue [15].…”
Section: Discussioncontrasting
confidence: 57%
“…We utilized healthy swine that did not have any bladder pathology, given that no porcine bladder cancer model exists presently. Healthy urothelial mucosa has been shown to be less permeable than tumor tissue, hence we believe that intravesical chemotherapy with HT may actually result in an even greater increase of MMC absorption in patients with bladder cancer than demonstrated in our study [17]. Our findings deferred from van Valenberg et al, where they found that MMC concentration did not differ between the cold MMC group and radiofrequency induced MMC group in normal urothelial tissue [15].…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, the absorption spectrum of nanoparticles could shift depending on color, morphology, and size due to the gold plasmon resonance property [ 73 ]. Nanostructures with NIR photo thermal properties have ability to scatter light strongly, which has significant applications in biomedical imaging [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, by modifying the shape of GNPs, such as by using GNRs or hollow gold nanoshells, their resonance peak can be shifted toward the NIR spectrum (Loo et al, 2004). In this regard, various gold nanoparticle configurations have been employed to modify their photothermal and subsequently therapeutic efficiencies (Vats et al, 2017).…”
Section: Commonly Used Gold Nanoparticle Configurationsmentioning
confidence: 99%